Web Footprint of Charlie Chaplin: A Webometric Exploration of Online References and Cultural Memory - Mondal, Debdas (Journal of Data Science, Informetrics, and Citation Studies)
This study examines the cultural and digital presence of Charlie Chaplin across various online platforms to assess his enduring relevance in the 21st century. The objective is to analyze how Chaplin’s legacy is represented and preserved in digital and scholarly environments. Data were collected from general search engines, academic databases, cultural archives, media platforms, and social media networks to map the distribution and nature of Chaplin-related content. Domain analysis revealed a predominance of commercial (.com) sources (46%), followed by nonprofit (.org), academic (.edu), and governmental (.gov) sites, indicating a balanced mix of popular and credible contributions. Keyword and thematic mapping highlighted recurring terms, including “Silent film,” “Modern Times,” “The Tramp,” “Political satire,” and “Cultural icon.” Quantitative findings showed 6,200 mentions in Google Scholar and 2,250 in Scopus, reflecting substantial academic engagement. On popular platforms, YouTube hosted over 18,000 videos, Twitter/X around 65,000 posts, Instagram approximately 40,000 posts, and TikTok about 12,000 clips, illustrating widespread cultural participation and reinterpretation. The study concludes that Chaplin’s presence spans academic, cultural, and popular spheres, demonstrating how digital media sustain historical figures through continuous visibility and interaction. His legacy endures as both a subject of scholarly inquiry and a focal point of global digital culture.
Keywords: Popular Culture; Webometrics; Bibliometrics; Altmetrics; Political Satire; Cinema Studies; Digital Culture; Social Media Engagement.